2001
DOI: 10.1161/hy1101.099478
|View full text |Cite
|
Sign up to set email alerts
|

Genes Encoding Fibrinogen and Cardiovascular Risk

Abstract: Abstract-The role of fibrinogen in cardiovascular disease has been extensively studied, and meta-analyses have definitively confirmed that high levels of fibrinogen are associated with an increased risk of the disease. In recent years, several polymorphisms have been identified in the fibrinogen chain genes that contribute to determine the levels of fibrinogen in the general population. The fibrinogen ␤-chain gene has been more extensively studied because the ␤-chain synthesis is the limiting step in the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 56 publications
(63 reference statements)
2
42
0
2
Order By: Relevance
“…Therefore, in our opinion, two other probably synergistic functions of vasculature-derived IL-6 (rev. in 8) seem to be more conceivable: 1) endocrine activation of the hepatic acute-phase response provoking the release of strong risk factors for cardiovascular disease, such as C-reactive protein (30,31) and fibrinogen (32,33); and 2) local paracrine activation of monocytes and platelets favoring fibrinogen deposition and thrombus formation in the vessel wall. In the case of an endocrine function, it could be postulated that palmitate-induced vascular IL-6 secretion influences plasma IL-6 concentrations, but this remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our opinion, two other probably synergistic functions of vasculature-derived IL-6 (rev. in 8) seem to be more conceivable: 1) endocrine activation of the hepatic acute-phase response provoking the release of strong risk factors for cardiovascular disease, such as C-reactive protein (30,31) and fibrinogen (32,33); and 2) local paracrine activation of monocytes and platelets favoring fibrinogen deposition and thrombus formation in the vessel wall. In the case of an endocrine function, it could be postulated that palmitate-induced vascular IL-6 secretion influences plasma IL-6 concentrations, but this remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…6,26,27 The other explanation is that the age of our group is younger (less than 40 years), because the À455A allele has been associated with the progression of atheroma, that is associated with the elderly population studies. The H2H2 homozygote genotype (À455G/A) was not found in all the groups studied.…”
Section: Discussionmentioning
confidence: 92%
“…But was not found between MI and Stroke group, which did not agrees total with numerous epidemiological studies where plasma FG has been associated with thrombotic disease, atherosclerotic disease, and an increased risk of cardiovascular disorders, including ischemic heart disease and stroke. 6,7 That could be explained on the basis of the results that was found dealing with the b-chain polymorphisms À455G/A and À48C > T. In special, the À455G/A has been the most extensively studied clinically and the À455HH genotype is present in %10-20% of the population and is correlated with FG levels that are 10% higher than in individuals with the H1H1 genotype. 6,9,26 The influence of the b-FG chain gene has been more extensively studied, because the synthesis of this chain is the limiting step for the production of the mature protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-A substitution in the promoter region of β-fibrinogen has been found to be associated with an increase in plasma fibrinogen levels [17,18]. One study demonstrated that the β-fibrinogen 148 TT genotype was associated with genetic risk factors for carotid atherosclerosis [19].…”
Section: Discussionmentioning
confidence: 99%